Deforestación en la Península de Yucatán, los retos que enfrentar - Sánchez Aguilar, Rodolfo Luis; Rebollar Domínguez, Silvia (Instituto de Ecología, A.C., 2016)
Over the last few years an intense and increasing deforestation has been gradually taking place. As a consequence, this phenomenon has brought about a notorious reduction in both Mexican and world wide forest areas. This problem has also appeared in the Yucatán Península, one of the regions in México where these ecosystems can be found, especially the tropical rain forest. This paper presents figures for the Mexican rain forest areas, as well as deforestation rates, particularly in the three states of the Yucatán Península (Campeche, Quintana Roo and Yucatán), from a national and international point of view. Deforestation causes are detailed. The fact is, however, that the results of the deforestation turn this problem into a national and overwhelming issue. Corrective actions that need to be put in place to address this problem include an efficient forest management plan that strives for the contribution of native dwellers that own the land and provide an excellent resource of traditional  knowledge. This knowledge needs to be part of the current foresttechniques that are used in the national gavernmental programs of forest management.